2022
DOI: 10.1002/slct.202103927
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/ZIF‐8 Composite Beads Fabricated by In Situ Growth of MOFs Crystals on Chitosan Beads for CO2 Adsorption

Abstract: CO 2 responsive polymer chitosan is introduced to fabricate polymer/MOFs composite materials used to explore CO 2 adsorption and recyclability. Chitosan beads (CBs) are successively immersed in the solution of Zn 2 + and the solution of 2methylimidazole to fabricate chitosan/ZIF-8 composite beads (CBsZx) by in situ growth of ZIF-8 crystal on chitosan beads. CBsZx are characterized by powder XRD, FT-IR, SEM, TEM, TGA and BET. The morphology, size and distribution of the ZIF-8 crystals on CBsZx are tuned by adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…54 In the previous work in which there was in situ growth of ZIF-8 on pure CS to prepare CS/ZIF-8 composites, the ZIF-8 crystals displayed cubic, hexagonal, and rhombic dodecahedral shape, which were extremely similar to the morphology of the pure ZIF-8 crystals prepared under the same conditions. 28 In the current paper, CGs were crosslinked with different crosslinking agents before providing heterogeneous nucleation sites for the ZIF-8 crystals. This result indicated that the chemical construction of CS played a key role in the nucleation of the ZIF-8 crystal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 In the previous work in which there was in situ growth of ZIF-8 on pure CS to prepare CS/ZIF-8 composites, the ZIF-8 crystals displayed cubic, hexagonal, and rhombic dodecahedral shape, which were extremely similar to the morphology of the pure ZIF-8 crystals prepared under the same conditions. 28 In the current paper, CGs were crosslinked with different crosslinking agents before providing heterogeneous nucleation sites for the ZIF-8 crystals. This result indicated that the chemical construction of CS played a key role in the nucleation of the ZIF-8 crystal.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper, CS/ZIF-8 composite beads were constructed by an in situ growth method. 28 The coordination of the amino groups on the CS skeleton with Zn 2+ and the self-emulsifying properties of CS played a key role in the in situ growth of the ZIF-8 crystals. However, the distribution of crystals on the surface of CS bead was poor, which may be due to the neglect of factors affecting the non-homogeneous nucleation of the crystals.…”
Section: Introductionmentioning
confidence: 99%
“…This result and phenomenon were also identified in our previous paper. 23 In the current paper, Zn 2+ could be coordinated with both the oxygen-containing functional groups (-COOH, -OH) of GoG and benzimidazole to grow ZIF-7 crystals on the networks of GoG. When the concentration of Zn 2+ was regulated in the range from 0.05 to 0.067 mol L À1 and the molar ratio of Zn 2+ to benzimidazole was kept as 4 : 25, ZIF-7 crystals were well grown on GoG to fabricate Z 1 @GoG and Z 0.8 @GoG.…”
Section: Resultsmentioning
confidence: 99%
“…22 In particular, introducing CO 2 responsive polymers enhanced the adsorption capacity of MOFs for CO 2 . 23,24 Graphene and its derivative were also integrated with MOFs to fabricate graphene/MOF composite materials, which had superior physiochemical properties and were applied in gas adsorption, photocatalysis, electrochemical energy conversion, and oil-water separation. 25,26 Graphene is a two-dimensional (2D) carbon allotrope that can be viewed as both a single atom-thick carbon sheet and a macromolecule with molecular weights of more than 10 6 -10 7 g mol À1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation